A Simply Marvellous Reaction: Autonomous Sensory Meridian Response and the Desk Tutorial. (1st March 2018) - Morris, Mark
Abstract : Mark Morris, Head of Teaching and Learning at the Architectural Association in London, has honed his career on imaginative insights into the architectural profession, its modes of representation, its fetishes and its means of education. Here he explores autonomous sensory meridian response (ASMR) – the soothing yet sensual, pleasurable cascades of happiness of small repetitive gestures, motions and sounds, such as the scrape of a paint knife on canvas or the comfort of a desk crit/tutorial – and its associated 'braingasms'.